2012
DOI: 10.1186/1475-2875-11-285
|View full text |Cite
|
Sign up to set email alerts
|

The extravascular compartment of the bone marrow: a niche for Plasmodium falciparum gametocyte maturation?

Abstract: BackgroundPlasmodium falciparum immature gametocytes accumulate in the bone marrow, but their exact location in this tissue remains unclear.MethodsThe stage and deposition pattern of gametocytes was analysed on histological sections of a bone marrow sample collected in a patient with subacute P. falciparum malaria.ResultsA majority (89%) of immature stages II to IV gametocytes and a minority (29%) of mature stage V gametocytes were observed in extravascular spaces.Discussion and conclusionThese observations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 11 publications
5
89
0
Order By: Relevance
“…Postmortem case studies from the early 1900s (Marchiafava and Bignami 1894;Thomson and Robertson 1935) and more recent field and clinical reports in the last two decades Farfour et al 2012;Aguilar et al 2014) have confirmed the presence of P. falciparum immature gametocytes in the spleen and bone marrow of malaria infected patients. Notably, a recent systematic histological and transcriptional analysis of autopsy tissues from children who died from cerebral malaria revealed gametocyte enrichment in the bone marrow parenchyma in which they are predominantly localized to the erythroblastic islands , suggesting that sexual stage development can occur in erythroid progenitor cells during infection.…”
Section: Sequestration Of Transmission Stagesmentioning
confidence: 91%
See 2 more Smart Citations
“…Postmortem case studies from the early 1900s (Marchiafava and Bignami 1894;Thomson and Robertson 1935) and more recent field and clinical reports in the last two decades Farfour et al 2012;Aguilar et al 2014) have confirmed the presence of P. falciparum immature gametocytes in the spleen and bone marrow of malaria infected patients. Notably, a recent systematic histological and transcriptional analysis of autopsy tissues from children who died from cerebral malaria revealed gametocyte enrichment in the bone marrow parenchyma in which they are predominantly localized to the erythroblastic islands , suggesting that sexual stage development can occur in erythroid progenitor cells during infection.…”
Section: Sequestration Of Transmission Stagesmentioning
confidence: 91%
“…Transmission-blocking intervention strategies targeting sexual stages should take into account molecular targets including the genetic pathways of sexual conversion, sequestration mechanisms, intercellular parasite communication mechanisms, and gametocyte deformability. Increasing evidence in recent years point to the existence of a niche for gametocyte development in the extravascular environment of bone marrow (and presumably in the spleen) (Farfour et al 2012;Aguilar et al 2014;Joice et al 2014) acting as the parasite's hideout. Identification of stage-specific markers and development of novel tools to study sequestration of immature gametocytes are warranted.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, achievement of malaria elimination requires development of novel strategies targeting the parasite sexual stages (gametocytes) that are responsible for transmission to mosquitoes. Plasmodium falciparum immature gametocyteinfected erythrocytes (GIEs) sequester in the human bone marrow, [1][2][3] and appear only as mature stages in the peripheral blood where they are accessible for mosquitoes that ensure transmission. Release into the peripheral blood is accompanied by an increase in GIE deformability that allows mature stages to persist several days in the bloodstream and avoid the clearance by the spleen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gametocytes in other species are round in shape, whereas P. falciparum gametocytes develop with five morphologically distinct stages, and the final mature gametocytes take a crescent form, where this parasite derived its name (Carter and Graves, 1988;Sinden, 1998). For P. falciparum, only the youngest stage-I and mature gametocytes are observed in blood circulation, whereas other immature stages of gametocytes are sequestered in the bone marrow and possibly the spleen (Farfour et al, 2012;Joice et al, 2014). These distinctions in gametocyte development between P. falciparum and other malaria parasites prompted us to analyze the functions of PfPuf1 during gametocytogenesis in P. falciparum.…”
Section: Introductionmentioning
confidence: 99%